INFLUENCE OF PUBLIC ENLIGHTENMENT PROGRAMMES OF THE FEDERAL ROAD SAFETY COMMISSION ON COMMERCIAL DRIVERS' BEHAVIOUR IN URBAN CENTRES IN SOUTHWESTERN, NIGERIA (2014)
Commercial vehicle drivers' behaviour on urban roads serves as the primary cause of most Road Traffic Accidents (RTAs). The Federal Road Safety Commission (FRSC), therefore, through its public enlightenment programmes (PEP) promoted sustainable good driving habits among these drivers. Previous studies on the reduction of RTAs have focused more on the drivers, vehicles, and infrastructural facilities without considerations for the PEP of the FRSC. This study, therefore, investigated the influence of FRSC's public enlightenment programmes on commercial drivers' behaviour (CDB) in urban centres in Southwestern Nigeria. The descriptive research design was adopted. The multi-stage sampling techniques was used in selecting 1,179 commercial drivers, 100 principal officers' from National Union of Road Transport Workers; 111 Road Transport Employers Association of Nigeria members, 174 Association of Luxury Bus Owners of Nigeria members, who had once attended FRSC's PEP and 20 FRSC's Officials from 28 motor parks in selected centres: Lagos, Akure, Ibadan and Abeokuta. Drivers' Perception of FRSC's Public Enlightenment Programme Inventory (r=0.83), Commercial Drivers Behaviour Inventory (r=0.92); and Commercial Drivers's Compliance Inventory (r=0.88) were used. These were complemented with 12 and six sessions each of Focus Group Discussion and Key Informant Interview with commercial drivers and FRSC officials. Five research questions were answered and two hypotheses tested at p?0.05.Data were analysed using descriptive statistics, Pearson's product moment correlation and multiple regression and content analysis. There was a significant joint effect of PEP on CDB (F (5, 1159) =519.53); and contributing 86.7% to the variance in CDB. The PEP on Radio (?=0.69), motor park rallies and road safety lectures (?=.678), PEP on Television (?=-.251), FRSC's Videos and Films (?=.133) and FRSC's handbills, posters and billboards (?=-.115) contributed to CDB. Also, PEP on Radio (r=.699), motor park rallies and road safety lectures (r=.668), PEP on Television (r=.237), FRSC's handbills, posters and billboards (r=.219) and FRSC's Videos and Films (r=.153) correlated with CDB. Content of PEP (r=.205), delivery strategies (r=.176), quality of resource personnel (r=.152), PEP timing (r=.113) and language of instruction (r=.089); all correlated with CDB. Also personal characteristics of commercial drivers predicted their compliance to PEP (F(9, 1155)=449.01); while experience (?=.211), marital status (?=.144), age (?=-.109), training on driving techniques (?=-.124), frequency of PEP attendance (?=.098), level of education (?=.023) and sex (?=-.015) contributed to compliance with PEP. The commercial drivers revealed that PEP is mostly restricted to the last quarter of the year and, is solely implemented by the FRSC without contributions and assistance from other governmental agencies and private initiatives. The public enlightenment programmes on radio, motor park rallies and road safety lectures positively influenced commercial drivers' behaviour. There is therefore the need to ensure that these programmes are implemented. Also, the language of instruction must be taken into consideration to cover all stakeholders.